Design for Multiplicity: Diving into the transdisciplinary nature of design processes - Matteo Vignoli; Arzu Gönenç Sorguç; Luca Iandoli; Anita Kocsis; Assaf Krebs (CERN IdeaSquare Journal of Experimental Innovation, 2023)
The contributions in this issue, selected from the ones presented at the DFGN.R 2023, a two-day event hosted at the METU Design Factory in Ankara, Turkey, and organized by the Design Factory Global Network, represent a broad cross-section encompassing various fields such as phenomenology, social theory, psychology, philosophy, artificial intelligence, and art, resonating with the principles of 21st Century learning and the United Nations’ Sustainable Development Goals, supporting the changing expectations of academics in producing alternative research outcomes in collaborative, practice-based research. These contributions offer valuable insights into how designers and innovators navigate the ever-expanding landscape of challenges and opportunities in multiple fields, elevating pedagogy and enhancing the art and science of learning, thinking, and doing.